Fotodziennikarskie naruszanie dуbr osobistych [Photoreporters against personal rights] - Misztal, Małgorzata (Biuletyn Edukacji Medialnej [Media Education Bulletin], 2008)
Privacy and alleged invasions of privacy by the media especially by the photograph are central issues in the ethics of journalism. Clearly, we live in a society that values personal privacy, and is concerned about intrusions into privacy from whatever source, including the media. Yet, perhaps paradoxically, we also live in a society that thrives on publicity, or at least one in which many individuals depend on publicity for their lives and activities.
https://katalog.adlr.link/Record/ai-53-177429